Respuesta :
Answer:
[tex]y=84[/tex]
Step-by-step explanation:
[tex]\left(\frac{1}{3}\right)y+11=\left(\frac{1}{2}\right)y-3[/tex]
Use distributive property.
[tex]\frac{1}{3}y+11=\frac{1}{2}y-3[/tex]
[tex]\frac{1}{3}y+11-11=\frac{1}{2}y-3-11[/tex]
[tex]\frac{1}{3}y=\frac{1}{2}y-14[/tex]
[tex]\frac{1}{3}y-\frac{1}{2}y=\frac{1}{2}y-14-\frac{1}{2}y[/tex]
[tex]-\frac{1}{6}y=-14[/tex]
[tex]\left(-\frac{1}{6}y\right)\left(-6\right)=\left(-14\right)\left(-6\right)[/tex]
[tex]y=84[/tex]
Answer:
y = 84
Step-by-step explanation:
1) 1/3y + 11 = 1/2y - 3
2) Add 3 to both sides
3) 1/3y + 14 = 1/2y
4) Subtract 1/3y from both sides
5) 14 = 1/6y
6) Multiple the reciprocal of the coefficient (1/6), which is 6 by both sides
7) 84 = y